English Teaching Through Literature-Based Instruction: What do Teachers Experience? - Utami, IGA Lokita Purnamika; Mahardika, I Gusti Ngurah Agung (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
Literature-based instruction is one of the methods that the teacher can used in teaching English to improve student’s four basic skills in English. As a result, this paper aimed to investigate a) to identify the procedures used by teacher in implementing literature-based instruction during distance learning to improve four basic English skills in the classroom at Gandhi Memorial International School, b) to analyze the challenges faced by teacher in implementing literature- based instruction during distance learning at Gandhi Memorial International School. The implementation of Literature-Based Instruction was carried out for Primary International School grade 5 at Gandhi Memorial International School. This study used qualitative research as a research method. The subject of this research was an English teacher in class 5B at Gandhi Memorial International School. Data were collected using an observation checklist and interview guidelines. The result of the data that had been collected from the first question was that the procedure carried out by the teacher is to carry out three stages, namely; pre-activity, whilst activity, and post-activity. Then, the findings for the second research question were that there are three challenges that teachers encountered, namely; time constraints, differentiated instructions, and various assessment rubrics.